ANALISIS SWOT DAN STRATEGI PENGEMBANGAN DESTINASI WISATA PANTAI RUMBIA DI KABUPATEN MINAHASA - Merry H Adrah (Jurnal Ilmu Pariwisata, 2024)
This study aims to analyze development strategies for Rumbia Beach as a leading tourism destination in Minahasa Regency, North Sulawesi, Indonesia. The methods used include field observations, interviews with local stakeholders, and SWOT analysis. The results of the study show that Rumbia Beach has significant tourism potential with its natural beauty, but its management is not yet optimal. Some weaknesses found include a lack of facilities, promotion, and poor road access. The proposed development strategies include improving infrastructure and facilities, promoting tourism, empowering local communities, and collaborating with various stakeholders. By implementing these strategies, it is hoped that Rumbia Beach can develop into an attractive and sustainable tourism destination, which will ultimately increase the income of local communities and contribute to the local economy.